2007
DOI: 10.1088/1126-6708/2007/02/066
|View full text |Cite
|
Sign up to set email alerts
|

Analytic continuation from imaginary to real chemical potential in two-color QCD

Abstract: The method of analytic continuation from imaginary to real chemical potential is one of the most powerful tools to circumvent the sign problem in lattice QCD. Here we test this method in a theory, two-color QCD, which is free from the sign problem. We find that the method gives reliable results, within appropriate ranges of the chemical potential, and that a considerable improvement can be achieved if suitable functions are used to interpolate data with imaginary chemical potential.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
75
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 55 publications
5
75
3
Order By: Relevance
“…In Ref. [11], in particular, a high-precision numerical analysis in SU(2) (or 2-color QCD) with n f £ 8 degenerate staggered fermions has shown that, for temperatures above the pseudo-critical one at zero chemical potential, the extrapolation to real µ improves considerably if ratio of polynomials are used instead of simple polynomials in interpolating the behavior with imaginary µ of some test observables, this validating a proposal formulated in Ref. [12].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In Ref. [11], in particular, a high-precision numerical analysis in SU(2) (or 2-color QCD) with n f £ 8 degenerate staggered fermions has shown that, for temperatures above the pseudo-critical one at zero chemical potential, the extrapolation to real µ improves considerably if ratio of polynomials are used instead of simple polynomials in interpolating the behavior with imaginary µ of some test observables, this validating a proposal formulated in Ref. [12].…”
Section: Introductionsupporting
confidence: 53%
“…A control on the systematics of the method of analytic continuation and possible insights for its improvement can be achieved by testing it in theories which do not suffer the sign problem, by direct comparison of the analytic continuation with Monte Carlo results obtained directly at real µ [4,9,10,11]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, importance sampling requires positive weights in the partition function In the last few years we approached the sign problem by the method of analytic continuation [2][3][4]. To this purpose we started our investigations [5][6][7] from some special cases where Monte Carlo simulations are both feasible at real and at imaginary chemical potential. The reason was to have the possibility to test the results of the analytical continuation by means of direct simulations at real chemical potential.…”
Section: Introductionmentioning
confidence: 99%
“…Various possibilities have been explored to circumvent the problem, like reweighting techniques [1,2,3], the use of an imaginary chemical potential either for analytic continuation [4,5,6,7,8,9,10] or for reconstructing the canonical partition function [11,12,13], Taylor expansion techniques [14,15] and non-relativistic expansions [16,17,18]. The same is not true in the case of a finite isospin density, i.e.…”
Section: Introductionmentioning
confidence: 99%